The Application of the RNA Interference Technologies for KRAS: Current Status, Future Perspective and Associated Challenges - Shao, Yu-Ting; Ma, Li; Zhang, Tie-Hui; Xu, Tian-Rui; Ye, Yuan-Chao; Liu, Ying (Current Topics in Medicinal Chemistry, 2019)
KRAS is a member of the murine sarcoma virus oncogene-RAS gene family. It plays an important role in the prevention, diagnosis and treatment of tumors during tumor cell growth and angiogenesis. KRAS is the most commonly mutated oncogene in human cancers, such as pancreatic cancers, colon cancers, and lung cancers. Detection of KRAS gene mutation is an important indicator for tracking the status of oncogenes, highlighting the developmental prognosis of various cancers, and the efficacy of radiotherapy and chemotherapy. However, the efficacy of different patients in clinical treatment is not the same. Since RNA interference (RNAi) technologies can specifically eliminate the expression of specific genes, these technologies have been widely used in the field of gene therapy for exploring gene function, infectious diseases and malignant tumors. RNAi refers to the phenomenon of highly specific degradation of homologous mRNA induced by double-stranded RNA (dsRNA), which is highly conserved during evolution. There are three classical RNAi technologies, including siRNA, shRNA and CRISPR-Cas9 system, and a novel synthetic lethal interaction that selectively targets KRAS mutant cancers. Therefore, the implementation of individualized targeted drug therapy has become the best choice for doctors and patients. Thus, this review focuses on the current status, future perspective and associated challenges in silencing of KRAS with RNAi technology.
Keywords: Oncogene